2019
DOI: 10.3390/molecules24101882
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of 4″,6″-Disubstituted Amphiphilic Kanamycins

Abstract: Amphiphilic kanamycins derived from the classic antibiotic kanamycin have attracted interest due to their novel bioactivities beyond inhibition of bacteria. In this study, the recently described 4″,6″-diaryl amphiphilic kanamycins reported as inhibitors of connexin were examined for their antifungal activities. Nearly all 4″,6″-diaryl amphiphilic kanamycins tested had antifungal activities comparable to those of 4″,6″-dialkyl amphiphilic kanamycins, reported previously against several fungal strains. The minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Collectively, all results suggested that amphiphilic aminoglycosides derived from neamine are interesting molecules for the development, in the future, of new antibiotics targeting bacterial membranes and/or tools for the study of the dynamics of bacterial membranes. How these activities could be extended to antiviral [70] or antifungal [71][72][73] activities and what are the strategies to block LPS biogenesis [74] should also be explored and could open new avenues based on the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, all results suggested that amphiphilic aminoglycosides derived from neamine are interesting molecules for the development, in the future, of new antibiotics targeting bacterial membranes and/or tools for the study of the dynamics of bacterial membranes. How these activities could be extended to antiviral [70] or antifungal [71][72][73] activities and what are the strategies to block LPS biogenesis [74] should also be explored and could open new avenues based on the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Such AAGs target bacterial and/or fungal membranes. The identification of non-antibacterial antifungal AAGs targeting fungal membranes demonstrates that the main targets of AAGs can be discriminated [ 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. This selectivity could be found in the difference between monoalkylated and di- or tri-alkylated derivatives of similar lipophilicities.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the first antifungal non-antibacterial AAGs identified were KAN derivatives. Their development, through the delineation of structure–activity relationships, led to the novel antifungal agent K20 ( Figure 13 ), which is capable of inhibiting many fungal species such as Fusarium graminearum , the causal agent in wheat Fusarium head blight (FHB) [ 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Plasma membrane permeabilization is probably the principal antifungal mechanism of action of AAGs, leading to the suggestion that they mechanistically and structurally comprise a novel class of antifungal agents [ 121 , 124 , 127 ].…”
Section: Other Biological Activities Of Aagsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphiphilic aminoglycosides particularly kanamycins attracted considerable interest for reviving these old drugs and by structural modifications turning them into antifungal agents [8]. They offer new options for fighting fungal pathogens and are examples of how to confront new therapeutic challenges [8,[22][23][24]. The antibacterial to antifungal conversion of aminoglycosides goes back to the alkyl modification of old drugs, turning them into agrofungicides [25].…”
Section: Discussionmentioning
confidence: 99%